Handbook of Clinical Rating Scales and Assessment in Psychiatry and Mental Health - Baer, Lee.; Blais, Mark A. (Current Clinical Psychiatry, 2010)
Psychiatric clinicians should use rating scales and questionnaires often, for they not only facilitate targeted diagnoses and treatment; they also facilitate links to empirical literature and systematize the entire process of management. Clinically oriented and highly practical, the Handbook of Clinical Rating Scales and Assessment in Psychiatry and Mental Health is an ideal tool for the busy psychiatrist, clinical psychologist, family physician, or social worker. In this ground-breaking text, leading researchers provide reviews of the most commonly used outcome and screening measures for the major psychiatric diagnoses and treatment scenarios. The full range of psychiatric disorders are covered in brief but thorough chapters, each of which provides a concise review of measurement issues related to the relevant condition, along with recommendations on which dimensions to measure and when. The Handbook also includes ready-to-photocopy versions of the most popular, valid, and reliable scales and checklists, along with scoring keys and links to websites containing on-line versions. Moreover, the Handbook describes well known, structured, diagnostic interviews and the specialized training requirements for each. It also includes details of popular psychological tests (such as neuropsychological, personality, and projective tests), along with practical guidelines on when to request psychological testing, how to discuss the case with the assessment consultant and how to integrate information from the final testing report into treatment. Focused and immensely useful, the Handbook of Clinical Rating Scales and Assessment in Psychiatry and Mental Health is an invaluable resource for all clinicians who care for patients with psychiatric disorders.